'This Is My Body': Corporeality, Emotional Intelligence, and the Pastoral Care of Men - Kummer, Armin (Louvain studies, 2023)
This article examines how insights from feminist theology and scholarship on men and masculinities can transform the pastoral care of men by focusing on corporeality and emotional intelligence. It highlights the pioneering contributions of feminist theologians, who have revalued the role of the body in theology, and explores how these insights challenge the traditional cognitive focus of pastoral care. The article outlines how men have been conditioned to adopt restrictive emotionality, leading to a disconnection from their bodies and emotions. Such disembodiment is linked to a range of personal and societal issues, including relational problems, mental health struggles, and violence. By drawing on feminist retrieval of corporeality and research on emotional deficits in men, the article proposes a pastoral care model that is embodied, affective, relational, and experiential. This model addresses the need for men to reconnect with their bodies and emotions, fostering emotional intelligence through practices such as mindfulness, creative interventions, and relational activities. The article suggests that these approaches can lead to more holistic care that supports men in developing healthier relationships, emotional awareness, and spiritual growth. The conclusion underscores the scholarly and societal implications of this model, advocating for broader changes in pastoral care practices and suggesting that fostering emotional intelligence in men can have wide-reaching benefits for both individuals and communities.